Reactions of 1-Trifluoromethylprop-2-yne 1-Iminium Salts with Nitroanilines: Synthesis of 4-Trifluoromethylnitroquinolines and 1,2,3-Trisubstituted 5-Trifluoromethylpyrroles - Seitz, Bianca; Schneider, Thomas; Majstorovic, Nikola; Fleischmann, Maximilian; Maas, Gerhard (Synthesis, 2021)
A variety of 4-trifluoromethylquinolines bearing an aryl (or cyclopropyl, tert-butyl, trimethylsilyl) group at C-2 and a nitro group at ring position 6, 7 or 8 have been prepared in good to high yields from 3-substituted 1-(trifluoromethyl)prop-2-yne 1-iminium triflate salts and o-, m- or p-nitroaniline. These reactions include an aza-Michael reaction at room temperature followed by an intramolecular electrophilic aromatic substitution step, which requires additional thermal activation in most cases. In contrast, the conjugate addition of 2,4-dinitroanilines at the acetylenic iminium ions proceeds much more slowly and some of the adducts can be converted thermally into 2-(2,4-dinitrophenyl)-5-trifluoromethylpyrroles. Analogously, 2-(4-pyridyl)-5-trifluoromethylpyrroles were obtained from 3-aryl-1-(trifluoromethyl)propyniminium salts and 4-aminopyridinium triflate. A novel variation of the Truce–Smiles rearrangement is probably involved in the formation of these pyrroles.
Keywords: iminium salts; pyrroles; quinolines; fluoroorganic compounds; trifluoromethylated building blocks